2020
DOI: 10.21786/bbrc/13.7/19
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Awareness on Various Suturing Techniques Used in Minor Oral Surgeries Among Dental Students

Abstract: There are oral surgical procedures that are part of the broad scope of general dentistry. These include routine oral surgery such as the extraction of teeth, suturing wounds, and biopsying suspicious soft tissue lesions. The ability to suture is one of the essential skills required of anyone planning to perform surgery.Learning to suture in an expert manner requires an understanding of the proper techniques and dedicated practice. The aim of the study is to evaluate the knowledge and awareness on various sutur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…Multifilament sutures tend to have a higher risk of stimulating infection when compared to monofilament sutures because they may enhance bacterial adhesion to adjacent sterile regions through capillary action, hence boosting the infection process. [ 32 33 ] Another study by Reddy[ 34 ] revealed that when questioned if they were aware of the available options in dentistry, 91% of the clinicians were aware and only 9% were not, which is identical to the results obtained in our study and thus revealed that majority of the test population were conscious of the different suture techniques.…”
Section: Discussionsupporting
confidence: 86%
“…Multifilament sutures tend to have a higher risk of stimulating infection when compared to monofilament sutures because they may enhance bacterial adhesion to adjacent sterile regions through capillary action, hence boosting the infection process. [ 32 33 ] Another study by Reddy[ 34 ] revealed that when questioned if they were aware of the available options in dentistry, 91% of the clinicians were aware and only 9% were not, which is identical to the results obtained in our study and thus revealed that majority of the test population were conscious of the different suture techniques.…”
Section: Discussionsupporting
confidence: 86%
“…A study by Reddy and Aishwarya Reddy[ 44 ] stated that about 91% of dental students were aware of the various suturing techniques. In our study, about 96% were aware of the Vicryl suture material.…”
Section: Discussionmentioning
confidence: 99%